An Odontometric Approach for Estimation of Stature in Indians: Cross- Sectional Analysis - Yadav, Achla Bharti (J Clin Diagn Res, 2016)
INTRODUCTION: Height/stature is one of the useful anthropometric parameter for individual identification. Correlation of stature to long bones, even fragmentary bones is frequently reported among various populations. As teeth have the advantage of being composed largely of hard tissue which is relatively indestructible, the careful study of these can enable reliable determination of stature of the person in life. AIM: The present study was designed to elucidate the anthropometric correlation of tooth dimensions with stature and also devises regression formulae. MATERIALS AND METHODS: This study was carried out on 361 Indian students (151 males and 210 females) in the age range of 21- 45 years to estimate stature using odontometry. Stature and tooth measurements were taken on each partcipant following standard methods and techniques. Karl Pearson’s correlation co-efficient and linear regression was used to estimate stature. RESULTS: Regression analysis showed that the canine width can aid in estimation of stature as an adjunct when only teeth are available for identification. CONCLUSION: Tooth dimensions can be used only as a supplementary approach for the estimation of stature but with caution.